Identity of historical areas of a city: interaction between nature and man - Dijokienė, Dalia; Paškauskienė, Aurelija (Landscape Architecture and Art, 2022)
The article discusses the preservation of urban peculiarity, visual uniqueness and cultural identity in the world affected by globalisation processes. First of all, the urban identity as such is discussed, a study of literary sources helps identify factors that shape urban identity. Tangible and intangible factors are distinguished. Second, in order to reveal the problems of identification and fostering of the identity of historical parts of cities and to verify the urban identity shaping methodology described in this article, historical suburbs of Vilnius in the southeast part of the Old Town are analysed in detail. The performed research of peculiarities of the urban fabric of the historical suburbs has showed very vividly that both the man made physical environment and the features of the natural environment present are significant for urban identity. In the studied suburbs, expressive terrain, also a river and its valley play a significant role for the formation and identity of a place. Man made built-up, ensembles, street routes and even the built-up function adapted to natural conditions. The close interaction between natural conditions and human activities has led to the identity of these historical territories. It is noted that urban identity should not be perceived as unchanging – it is a process that is shaped rather deliberately. Urban design, architecture and landscape architecture are activities that help create urban identity.